Amino acid sequence of a human leukocyte interferon. - Levy, W P (1981)
The primary structures of three major species of human leukocyte interferon differ from the structure predicted from the DNA sequence of recombinants containing leukocyte interferon-coding regions. Compared to the recombinant interferon produced in bacteria, three of the purified natural proteins isolated from leukocytes lack the 10 COOH-terminal amino acids suggested by the DNA sequence.